Economical Safety Issue Research - Pozhyeva, T.O. (Економічний вісник Донбасу, 2013)
The article pays your attention not only to the economical safety role of legal entity but to its compounds. The author admits the vital importance of this role in the management system and determines the reasons causing negative feedback of the economical safety and shows the way to come them over.